A critical review on chemical constituents and pharmacological effects of Lilium - Pengyu Wang; Jian Li; Fatma Alzahra K. Attia; Wenyi Kang; Jinfeng Wei; Zhenhua Liu; Changqin Li (Food Science and Human Wellness)
Genus Lilium is famous for edible and medicinal function which is related to its chemical constituents and pharmacological effects. Chemical researches showed that genus Lilium genus mainly contains steroidal saponins, polysaccharides, alkaloids and flavonoids. Pharmacological effects of Lilium include anti-tumor, hypoglycemic, antibacterial, anti-oxidation, anti-depression and anti-inflammatory. This paper summarized chemical constituents and pharmacological effects of Lilium. Keywords: Lilium, Chemical constituents, Pharmacological effects